Transactional Associations Between Adolescents' Emotion Dysregulation and Symptoms of Social Anxiety and Depression: A Longitudinal Study. (October 2019) - Masters, Mitchell R.; Zimmer-Gembeck, Melanie J.; Farrell, Lara J.
Emotion dysregulation has been associated with increased risks for psychopathology. During adolescence when the onset of mental illnesses peak, emotion dysregulation may be particularly problematic. In this study, we examined transactional associations between young adolescents' self-report of their emotion dysregulation and symptoms of social anxiety and depression at three assessments over 3 years. Participants were 391 Australian students (56% female; 79% White/Caucasian) in Grades 6 to 8 followed until Grades 9 to 11. Using structural equation modeling (SEM), emotion dysregulation was a latent variable indicated by lack of emotional clarity, nonacceptance of emotional responses, impulse control difficulties, limited access to emotion regulation strategies, and difficulties engaging in goal-directed behavior. A sixth aspect of emotion dysregulation, lack of emotional awareness, which was not correlated with the other five subscales, was examined separately in the SEM. Transactional associations over time were identified between emotion dysregulation and symptoms of social anxiety and depression, with adolescents higher in emotion dysregulation at Time 1 (T1) reporting higher social anxiety and depressive symptoms between T1 and Time 2 (T2), and T2 emotion dysregulation predicting increases in adolescents' depression, but not social anxiety, symptoms from T2 to Time 3 (T3), after controlling for baseline symptoms. In addition, earlier social anxiety, but not depressive, symptom level at T2 was significantly associated with later emotion dysregulation between T2 and T3, after baseline emotion dysregulation was controlled. Furthermore, girls were higher in emotion dysregulation, social anxiety, and depression than boys, but sex did not moderate temporal links between emotion dysregulation and symptoms.